Intentions in communication - Cohen, Philip R.; Morgan, Jerry L.; Pollack, Martha E. (MIT Press, 1990)
Intentions in Communication brings together major theorists from artificial intelligence and computer science, linguistics, philosophy, and psychology whose work develops the foundations for an account of the role of intentions in a comprehensive theory of communication. It demonstrates, for the first time, the emerging cooperation among disciplines concerned with the fundamental role of intention in communication.The fourteen contributions in this book address central questions about the nature of intention as it is understood in theories of communication, the crucial role of intention recognition in understanding utterances, the use of principles of rational interaction in interpreting speech acts, the contribution of intonation contours to intention recognition, and the need for more general models of intention that support a view of dialogue as a collaborative activity.The contributors are Michael E. Bratman, Philip R. Cohen, Hector J. Levesque, Martha E.-Pollack, Henry Kautz, Andrew J. I. Jones, C. Raymond Perrault, Daniel Vanderveken, Janet Pierrehumbert, Julia Hirschberg, Richmond H. Thomason, Diane J Litman, James F. Allen, John R. Searle, Barbara J. Grosz, Candace L. Sidner, Herbert H. Clark and Deanna Wilkes-Gibbs. The book also includes commentaries by James F. Allen, W. A Woods, Jerry Morgan, Jerrold M. Sadock Jerry R. Hobbs, and Kent Bach.Philip R. Cohen is a Senior Computer Scientist at the Artificial Intelligence Center at SRI International and is a Senior Researcher with the Center for the Study of Language and Information; Jerry Morgan is Associate Professor, Department of Linguistics and Beckman Institute for Advanced Science and Technology at the University of Illinois; Martha E. Pollack is a Computer Scientist at the Artificial Intelligence Center at SRI International and is a Senior Researcher with the Center for the Study of Language and Information.-Intentions in Communication is included in the System Development Foundation Benchmark Series.
"A Bradford book."
Keywords: Communication.; Intention.; Speech acts (Linguistics); Pragmatics.; Discourse analysis.; elektronické knihy; electronic books